Students who have sex with teachers : a youth perspective from the Western Cape education region - Anderson, Valerie-Claire (Department of Social Development, 2014)
This thesis begins to explore the phenomenon, in the South African education system, of students who have sex with teachers. The study provides a more nuanced understanding of student-teacher sexual relationships, reporting on empirical research which explores the prevalence of the phenomenon, the circumstances in which it occurs and students' opinions. In doing so, this research contributes to a more complete picture of student-teacher sexual relationships, exploring a plurality of viewpoints, in order to inform policy and interventions.